Suatu Gambaran Pengetahuan Bencana Gempa Bumi pada Anak-anak Kelurahan Pedungan Denpasar Selatan Bali - Maharani, Nia (UNIB Press, 2024)
Indonesia is a country prone to natural disasters such as earthquakes. Every year natural disasters occur in several provinces of Indonesia. Bali is one of the provinces where earthquake often occur. Earthquake cannot be predicted when and where they will occur, so they can cause material and non-material losses. from an early age need to gain knowledge about earthquakes to minimize the danger of earthquakes. The aim of this research is to see how the picture or description of earthquake knowledge in young children is. This research used 5 children as respondents in Pedungan Village. Respondents' ages ranged from 6-8 years with different educational backgrounds st Children arting from kindergarten to elementary school. The data collection method used was the interview method by asking 5 basic questions each about earthquakes and volcanic eruptions and then analyzed univariately (Maharani, 2024). The results of the research show that there is still a lack of basic knowledge among children in Pedungan Subdistrict, so there is a need for outreach activities regarding these earthquake from schools and from local related agencies.